2011
DOI: 10.1002/tox.20769
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin‐inhibited migration and invasion in human osteosarcoma U‐2 OS cells is carried out by suppression of the matrix metalloproteinase‐2, ERK, and JNK signaling pathways

Abstract: Bufalin has been shown to exhibit multiple pharmacological activities, including induction of apoptosis in many types of cancer cell lines. Osteosarcoma is a type of cancer which is difficult to treat and the purpose of this study was to investigate the effects of bufalin on the migration and invasion of human osteosarcoma U-2 OS cells. The wound healing assay and Boyden chamber transwell assay were used for examining the migration of U-2 OS cells. Western blotting and gelatin zymography assays were used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
(52 reference statements)
3
34
0
Order By: Relevance
“…Therefore, it is expected that bufalin may be a novel target to reduce cancer cell metastasis. However, the anti-metastatic activity of bufalin has not yet been extensively investigated; to our knowledge, only one study has been published so far (34). In the present study, we found that bufalin significantly inhibited the migratory and invasive activity in T24 bladder carcinoma cells by enhancing TJ activity, downregulating MMP activity and modulating TJ-related proteins in vitro.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Therefore, it is expected that bufalin may be a novel target to reduce cancer cell metastasis. However, the anti-metastatic activity of bufalin has not yet been extensively investigated; to our knowledge, only one study has been published so far (34). In the present study, we found that bufalin significantly inhibited the migratory and invasive activity in T24 bladder carcinoma cells by enhancing TJ activity, downregulating MMP activity and modulating TJ-related proteins in vitro.…”
Section: Discussionmentioning
confidence: 47%
“…Bufalin induces cell cycle arrest, differentiation and apoptosis in many human cancer cells such as leukemia, gastric, colon, breast, endometrial and ovarian cancer and osteosarcoma cells (27)(28)(29)(30)(31)(32)(33). Recently, Chueh et al (34) demonstrated that bufalin inhibited migration and invasion in human osteosarcoma cells by downregulating the levels of MMP-2, extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) signaling pathways. However, the anti-metastatic effects of bufalin on cancer cells have not yet been thoroughly reported and knowledge of the molecular mechanisms involved is rudimentary and remains to be delineated.…”
Section: Introductionmentioning
confidence: 98%
“…Digitoxin and ouabain blocked HUVEC migration towards different growth factors: VEGF, bFGF, EGF, FBS plus ECGS. Inhibition of cell migration by several cardiac glycosides (ouabain, arenobufagin, bufalin, the cardenolide analogue UNBS1450) has been demonstrated in other cell types, in particular cancer cells, indicating that it might be a common biological effect of this class of drugs (Mijatovic et al , ; Li et al , ; Chueh et al , ; Magpusao et al , ). Interfering with cell migration in the tumour context affects several key processes for cancer development and progression such as angiogenesis, recruitment of inflammatory cells, tumour cells invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bufalin reduced MMP-2 and MMP-9 enzyme activities of U-2 OS cells. Bufalin also suppressed the protein level of MMP-2 and reduced the levels of mitogenactivated protein kinases (MAPKs) such as JNK1/2 and ERK1/2 signals in U-2 OS cells (Chueh et al, 2011).…”
Section: Osteosarcomamentioning
confidence: 99%